2021
DOI: 10.1007/s12144-021-01442-y
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative case study about overuse of digital play at home

Abstract: The prevalence of digital play devices, including tablets and smartphones, has led to overuse among some young children. The purpose of this research is to examine the overuse cases among young children. Participants of this qualitative case study were five children aged five to seven years, their parents, and a psychiatrist. The data were mainly obtained through semi-structured interviews. Interviews were further supported by close observations, a collection of digital play diaries, as well as an interview wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…This suggests that mobility and privacy are more valued than the quality of the display. Similar studies conducted in Turkey have also reported that approximately 70% of Internet users play online games at home (Ilgaz & İnci, 2020; Işıkoğlu et al, 2023).…”
Section: Literature Reviewsupporting
confidence: 70%
See 1 more Smart Citation
“…This suggests that mobility and privacy are more valued than the quality of the display. Similar studies conducted in Turkey have also reported that approximately 70% of Internet users play online games at home (Ilgaz & İnci, 2020; Işıkoğlu et al, 2023).…”
Section: Literature Reviewsupporting
confidence: 70%
“…This suggests that mobility and privacy are more valued than the quality of the display. Similar studies conducted in Turkey have also reported that approximately 70% of Internet users play online games at home (Ilgaz & İnci, 2020;Işıkoğlu et al, 2023). Labrador et al (2023) also concluded that the inclination towards online gaming, whether in an individual or group setting, was significantly higher among males, accounting for 57.0% of the participants, in contrast to females, who constituted a mere 14.4%.…”
Section: Patterns Of Using Video Gamesmentioning
confidence: 73%
“…For example, parental guidance and support can result in cognitive or social-emotional benefits and self-regulation in children’s digital engagement [ 25 ]. In contrast, restrictive strategies have no such helpful outcomes and are less effective in controlling digital use time [ 79 ]. Therefore, by encouraging active discussion and supporting early digital usage, parents could optimize the messages provided by positive digital content [ 80 ] and build children’s skills and agency [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that both children and adolescents spend a significant amount of time playing digital games in their daily lives (Işıkoğlu et al, 2021). However, games are not limited to the activities that students prefer to have a pleasant time in the last few years.…”
Section: Discussionmentioning
confidence: 99%